Effectiveness of Educaplay Games on Students' Cognitive Understanding in Mathematics Learning in Grade II at SDN Bugih 3 Pamekasan - Salsabila, Annisa; Maltufah, Nuriyanti (Widyagogik, 2025)
This study aims to evaluate the effectiveness of educational games utilizing the Educaplay platform in improving cognitive understanding of second- grade students in Mathematics at SDN Bugih 3 Pamekasan. The approach used was a quasi-experiment, with a one-group pretest-posttest design with 30 students as subjects. Multiple-choice tests were used as instruments to assess students' understanding before and after the intervention. The results of the Wilcoxon Signed-Rank test showed a significant difference between the pretest and posttest scores (p 0.05), indicating an increase in understanding after using Educaplay. Furthermore, the N-Gain analysis showed an average increase of 82.33%, which is included in the high category. These results indicate that combining interactive game-based learning effectively improves students' motivation, engagement, and conceptual understanding. Thus, Educaplay is recommended as an innovative alternative tool for elementary education.